Cluster Organizations in Praxis: Structural and institutional influences on a cluster-orientated promotion of economic development - Häfner, Karl (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Cluster organizations implement cluster policies and affect the outcome of them to a high degree. Their work is influenced by interactions with the promoted firms, political and other actors. A sound consultancy of cluster promotion should know these influences and take them seriously, because they shape the strengths, weaknesses and potentials of cluster organizations. This article examines how cluster organizations in Bavaria translate cluster theory into practical activities and how other actors influence them in the process. The influences are subdivided into institutional and structural factors. Institutional factors refer to social institutions that other actors impose on the organizations. It will be shown that these factors shape the work of cluster organizations to a high degree, but only seldom restrain it. The organizations positions and tasks within the wider economic promotion system constitute the structural factors. They confine the organizations towards networking activities and force them to cooperate with other promotional actors, if they want to provide a comprehensive cluster promotion.